ADOLESCENT POSTERIOR-SUPERIOR GLENOID LABRAL PATHOLOGY: DOES INVOLVEMENT OF THE BICEPS ANCHOR MAKE A DIFFERENCE?. Issue 4 (28th April 2020) - Hansen, Cody H.; Asturias, Alicia M.; Pennock, Andrew T.; Edmonds, Eric W.
Background: Adolescent athletes are at risk to sustain an injury to the posterior and superior labrum of the glenoid. Limited information is available regarding the outcomes of surgical intervention in this specific age cohort. Purpose: To compare those patients with pure posterior pathology and those with involvement of the biceps anchor (superior labrum anterior-posterior tears - SLAP) to determine risks for failure in the surgical management. Methods: A retrospective review was performed on all patients under the age of 19 years over an eight year period to identify those treated for superior and posterior labral pathology, followed by chart review, radiographic review and arthroscopic findings. Demographics and other variables were recorded, including: etiology (traumatic versus atraumatic), activity/sports (overhead versus non-overhead), involvement of the biceps anchor – crossing the 12 o'clock position (Posterior vs SLAP), associated pathologies, outcome scores (SANE – Self Assessment Numerical Evaluation versus PASS – Pediatric Adolescent Shoulder Score), and complications. Results: 48 patients (30 males, 18 females) with a mean age at surgery of 16.5 years (range 13.5 to 19) were identified that met criteria with a mean follow-up of 4.1 years (range 1.3 to 6.9). Nineteen subjects had SLAP tears, and 29 subjects had posterior tears. All but 2 regularly participated in sports at the time of their injury; of the athletes, 26 (56.5%) played an overhead sport and 20 (43.5%) played a non-overhead sport. The etiology of the injury was traumatic in 25 cases (52.1%), and atraumatic in 23 cases (47.9%). Outcome scores were not significantly different between etiology or type of sports played; but, the mean PASS score in the SLAP group was 88.7, compared to 76.2 in the posterior group (p=0.005) at final assessment. Only 1 SLAP patient failed management (5.3%) compared to 5 patients in the posterior only cohort (17.2%). Conclusion: SLAP tears have better outcomes and lower failure rates than posterior only tears in the adolescent population. Posterior-superior labral tears can occur in all sport types with multiple etiologies, but the only factor that appears to play a role in ultimate outcome is whether or not the tear crosses under the biceps anchor to the anterior side.